CAUSES AND CONSEQUENCES OF DEPOPULATION IN THE MUNICIPALITY OF KURŠUMLIJA - Vasiljević, Milen; Vukoičić, Danijela; Valjarević, Aleksandar (Bulletin of Natural Sciences Research, 2019)
The municipality of Kuršumlija is located in the South of Serbia, encompassing the area of 952 km². According to the census from 2011, it is inhabited by 19,213 people. During the last decades, the municipality is facing the rapid decrease in the number of inhabitants, caused by natural and social factors. The manuscript analyzes the demographic changes reflected in the migration and structure of population in the period after 1948, along with the beginning of the industrial development, to 2011, when the municipality experienced the crash of economy. The analysis established that the municipality of Kuršumlija became emigrational area, especially after the closure of large industrial facilities which were the pillars of development. The young ones and those able for work were forced to leave their hearths, in search for employment and survival. All the settlements of Kuršumlija were included in the negative demographic processes reflected in the constant decrease of population. Big problem was also the intensity of inhabitants’ ageing, and lessening of the percentage of young ones, which points out that the municipality is in the phase of the deepest demographic age. The worrying fact is that the tendency of the population rate decrease in the settlements of Kuršumlija ‘municipality is prolonged.